Determinants of Competitive Advantage for Sport Firms: Using Public Big Data in Korea - Iksu Jun; Hojun Sung; Juho Park; Hyun-Woo Lee (Journal of Applied Sports Management, 2022)
This study examines the determinants of competitive advantage with respect to economic performance of sport firms. Logit regressions estimated dependent variables of economic performance measures based on sales per capita of firms. Determinants of competitive advantage were estimated by efficiency indicators, organization characteristic indicators, and industry classification indicators. Increase in efficiency was a significant determinant of competitive advantage as well as organizational type, size of human resource, diversification of products, and sales growth rate. Operationalizing competitive advantage as outperforming the market average and better than the top 10%, the logit regression model provides means for sport firms to analyze industry data to evaluate their own performance. In particular, including efficiency estimates showed practical significance for market analysis.
Keywords: Competitive Advantage; Public Data; Data Analytics; Efficiency; Korean Sport Industry